RNA editing events and expression profiles of mitochondrial protein-coding genes in the endemic and endangered medicinal plant, Corydalis saxicola - Li, Cui; Liu, Han; Qin, Mei; Tan, Yao-jing; Ou, Xia-lian; Chen, Xiao-ying; Wei, Ying; Zhang, Zhan-jiang; Lei, Ming (Frontiers in Plant Science, 2024)
Corydalis saxicola, an endangered medicinal plant endemic to karst habitats, is widely used in Traditional Chinese Medicine to treat hepatitis, abdominal pain, bleeding hemorrhoids and other conditions. However, to date, the mitochondrial (mt) genome of C. saxicola has not been reported, which limits our understanding of the genetic and biological mechanisms of C. saxicola. Here, the mt genome of C. saxicola was assembled by combining the Nanopore and Illumina reads. The mt genome of C. saxicola is represented by a circular chromosome which is 587,939 bp in length, with an overall GC content of 46.50%. 40 unique protein-coding genes (PCGs), 22 tRNA genes and three rRNA genes were identified. Codon usage of the PCGs was investigated and 167 simple sequence repeats were identified. Twelve homologous fragments were identified between the mt and ct genomes of C. saxicola, accounting for 1.04% of the entire mt genome. Phylogenetic examination of the mt genomes of C. saxicola and 30 other taxa provided an understanding of their evolutionary relationships. We also predicted 779 RNA editing sites in 40 C. saxicola mt PCGs and successfully validated 506 (65%) of these using PCR amplification and Sanger sequencing. In addition, we transcriptionally profiled 24 core mt PCGs in C. saxicola roots treated with different concentrations of CaCl2, as well as in other organs. These investigations will be useful for effective utilization and molecular breeding, and will also provide a reference for further studies of the genus Corydalis.